MicroRNA-122-5p Inhibition Improves Inflammation and Oxidative Stress Damage in Dietary-Induced Non-alcoholic Fatty Liver Disease Through Targeting FOXO3 - Hu, Yiyi; Peng, Xuetao; Du, Guoping; Zhang, Zhiqiao; Zhai, Yingji; Xiong, Xingbo; Luo, Xiaoliang (Frontiers in Physiology, 2022)
Misregulated microRNA network has been emerging as the main regulator in non-alcoholic fatty liver disease (NAFLD). The deregulation of miR-122-5p is associated with the liver disease. However, the specific role and molecular mechanism of miR-122-5p in NAFLD remain unclear. Here, we reported that the high fat diet (HFD) or palmitic acid (PA) significantly upregulated hepatic miR-122-5p expression in vivo and in vitro. Inhibition of miR-122-5p suppressed lipids accumulation-induced inflammation and oxidative stress damage in PA treated L02 cells and HFD-induced fatty liver. The effect of the miR-122-5p inhibitor on NAFLD did not depend on insulin resistance-mediated PI3K/AKT/mTOR signaling pathway, but rather on the upregulation of its downstream FOXO3. Subsequently, we validated that miR-122-5p directly binds to the predicted 3′-UTR of FOXO3 to inhibit its gene expression. Conversely, silencing FOXO3 abolished the hepatic benefits of miR-122-5p inhibition to obese mice by decreasing the antioxidant enzymes activity of SOD. The present study provides a novel finding that FOXO3 was the target gene of miR-122-5p to attenuate inflammatory response and oxidative stress damage in dietary-induced NAFLD. Our study provided evidence to reveal the physiological role of miR-122-5p in dietary-induced NAFLD.